Keanekaragaman Jenis Semut (Hymenoptera: Formicidae) Di Resort Ranu Darungan Taman Nasional Bromo Tengger Semeru dan Pemanfaatannya sebagai Buku Ilmiah Populer - Nanda Bima Satria WR (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Ants are crucial to ecosystem balance, performing diverse roles as predators, decomposers, polinator, seed dispersers and ecosystem engineers. Their diversity is highly dependent on habitat characteristics and environmental conditions. This research is aimed to analyze ant species diversity through ecological indices (Shannon-Wiener, Evenness, Dominance), composition similarity, and correlation with abiotic factors, conducted at Ranu Darungan Resort in Bromo Tengger Semeru National Park (TNBTS),. The study also evaluated the feasibility of a derivative popular science book. Using the hand-collecting method in utilization and Jungle zones, 3581 individuals from 15 species and 4 subfamilies were identified. The utilization zone showed higher diversity (H′ =2.512) and evenness (E′ =0.8808) than the forest zone (H′ =2.209; E′ =0.701). Dominance was low in both zones (D<0.14) with high similarity between them (80%). Abiotic factors like temperature, humidity, and light intensity correlated with specific species. Canonical Correspondence Analysis (CCA) showed 4 forest zone species correlated with multiple abiotic factors, whereas 10 utilization zone species correlated with temperature. Principal Component Analysis (PCA) linked ant species with 15 plant species in the forest and 24 in the utilization zone. Finally, the popular science book developed from this research was validated as 'highly suitable' with an 88.6% feasibility score.
Reupload file repository 26 Maret 2026_Ratna
Keywords: Ants Diversity; Formicidae; Ranu Darungan; TNBTS; Popular Science Book